2010
DOI: 10.1097/01.hjh.0000379095.22930.9a
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Smoking and Glucose Metabolism in Patients With Hypertension: PP.17.169

Abstract: p < 0,05), increase of EF by 2,5% (p < 0,05) were accompanied with decrease of LVMI by 12,2% (p < 0,05). 12-month treatment with combination ramipril and lercanidipine didn't influenced on TC, LDL-C, HDL-C levels, but TG level had statistically significant decrease by 12,9% (p < 0,05), that became correspondent to recommended level for patients without type 2 diabetes -1,80 mmol/l. Level of fasting glucose in blood serum hadn't exposed to statistically significant changes.Conclusions: Hipotensive effect of ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…[ 33 ] Smokers and nonsmokers do not appear to influence glucose levels in patients with diabetes. [ 34 35 ] Similarly, in this study it was observed that most of the patients were nonsmokers; however, smoking as a variable was not found to be associated with glucose level change.…”
Section: Discussionsupporting
confidence: 49%
“…[ 33 ] Smokers and nonsmokers do not appear to influence glucose levels in patients with diabetes. [ 34 35 ] Similarly, in this study it was observed that most of the patients were nonsmokers; however, smoking as a variable was not found to be associated with glucose level change.…”
Section: Discussionsupporting
confidence: 49%